Comportamento estrutural de vigas mistas de aço e concreto com protensão externa - Nelsen, Anna Carolina Haiduk (2013)
This report investigates the structural behavior, procedures for analysis and design of externally prestressed steel-concrete composite beams. Based upon the requirements outlined in ABNT NRB 8800:2008 for conventional composite beams and in the literature review, a systematic procedure was developed to design of externally prestressed steel-concrete composite beams requested the positive bending moment. Was analyzed the main modes of global collapse, especially the ultimate limit state design (ELU), which may occur in this type of structure. Also, elaborated a parametric study aimed to analyze the influence of variation in the level of prestressing and the eccentricity of tendons, as well as the constructive methodology (pretensioning and posttensioning) adopted for the the prestressing steel profile that makes up the of steel-concrete composite beam. The parametric study showed that in both methods the predominant failure mode occurs in 2nd Stage of construction. In models of composite beams analyzed with application of pretensioned when the tendon is positioned above the bottom flange of the profile steel the failure mode occurred for the combined bending and axial compression .As for the composite beams evaluated with posttensioned, independent of the position of the tendon, the failure mode occurred in function of the bending moment more than the allowable flexural strength. However, it is noted that the level of prestressing can be adequately calculated to ensure that there is no loss of carrying capacity of the structure. It was also observed that regardless of the constructive methodology adopted, higher eccentricities result in higher bearing capacity for the steel beam, as exposed in the literature review. While in Brazil is largely unexplored, there was widespread interest in the international literature on the subject in question and their variances, giving rise to theoretical and experimental. Also been mentioned as potential applications in the design of new structures and the renovation and rehabilitation of existing structures.